Directed motivational currents: optimal productivity and long-term sustainability in second language acquisition - Ibrahim, Zana Ismail (2016)
This thesis is concerned with the issue of motivational intensity and sustainability in second language (L2) learning through investigating a recently-conceptualised phenomenon theorised by Dörnyei and colleagues (Dörnyei, Ibrahim, & Muir, 2015; Dörnyei, Muir, & Ibrahim, 2014) and termed Directed Motivation Currents (DMCs). The phenomenon is characterised by intensity of engagement, sustainability of effort, and positive affect, in which individuals display highly motivated goal-governed behaviour and achieve outcomes exceeding expectations set at the outset. DMCs are postulated to represent the optimal form of long-term engagement. The aims of this thesis were to investigate the DMCs in regard to their theoretical justification and empirical validation. The initial chapters present the argument for why the L2 motivation field needs a new motivational construct. It is posited that although aspects of DMCs are discussed in many existing theories, mainstream motivational psychology has not previously captured periods of motivational surges people experience in pursuit of valued personal visions. Accordingly, the main queries guiding this research were to examine what it was like to experience a DMC and what the motivational sources of such motivational drives were. Deploying a phenomenological method of data analysis, exploratory qualitative in-depth interviews were conducted with a number of students who had experienced, or were experiencing, a DMC, whether individually or as part of a group. In addition to providing empirical validation for the DMC phenomenon, results revealed what conditions led to a DMC, what a DMC-cycle entailed, and how DMCs made use of a salient structure. The findings suggested that developing a facilitative structure immediately upon a DMC launch was key to the longevity of the current in part due to the effect of behavioural routines and their role in ensuring continued engagement and protecting it from competing temptations. The findings also implied the central role of positive affect in altering the perception of effort and rendering volitional self-control dispensable. As a result of eudaimonic happiness and a sense of growth, the participants experienced positive affect whereby effort was enjoyed and engagement was sustained until goal attainment. However, what accounted for most of the positive affect was not the pleasure of engagement itself or feelings associated with merely learning a second language. Rather, happiness was due to the sense that one was going through a transformational process in which one’s image and identity, level of operation and skills, as well as one’s entire personal entity was being developed. This somewhat indirect link between personal growth and happiness through L2 learning was seen as a new, promising, but challenging area of research. The results also revealed that DMCs could be experienced by groups of learners and at various levels and timescales when combined energy was directed at a shared goal. Furthermore, it was argued that group DMCs were the ultimate form of group performance in large part due to their potential immunity from social loafing which prevents groups from functioning at their highest capacity. In summary, empirical evidence presented in this thesis suggested that long-term motivational momentum in DMCs was the outcome of optimal aggregation of motivational properties that jointly enabled individuals and groups to operate at their highest levels and achieve outstanding results in a fast-track pathway towards goal attainment. While in a DMC, due to the impact of positive affect and a functioning structure, renewable motivational energy is utilised, which empowers long-term and self-propelled engagement without the need for volitional self-regulatory measures. Once applied in L2 settings, DMCs are argued to provide an exceptionally powerful boost to language learners’ motivation and performance.